EUROPEAN EXPERIENCE IN WORKING WITH YOUTH AT-RISK GROUPS - Toshpulotov Shokhijakhon Eshpulotovich (International Journal of Business, Law and Political Science, 2025)
Objective: This study investigates integrated policy frameworks for supporting at-risk youth in Europe, with a focus on identifying critical components that enhance social inclusion and reduce delinquency. Method: Employing a qualitative, comparative case study design, the research analyzes national strategies and localized practices in Germany, the Netherlands, Sweden, and France through policy document reviews, expert interviews, and outcome assessments. Results: The analysis reveals three key success factors: early identification of at-risk youth, interdisciplinary coordination among education, health, and social services, and localized rehabilitation efforts. These integrated approaches have led to measurable improvements, including reduced youth delinquency rates, strengthened reintegration outcomes, and enhanced psychological and social well-being. Novelty: This article provides a systematic cross-national evaluation of multi-sectoral intervention models, contributing novel insights into the design and implementation of holistic support systems. The findings offer transferable policy lessons for other nations seeking to enhance youth protection mechanisms through early intervention and community-based collaboration.